Generation of Liposomes to Study the Effect of Mycobacterium Tuberculosis Lipids on HIV-1 cis- and trans-Infections - Pouget, Marion (Int J Mol Sci, 2021)
Tuberculosis (TB) is the leading cause of death among HIV-1-infected individuals and Mycobacterium tuberculosis (Mtb) co-infection is an early precipitate to AIDS. We aimed to determine whether Mtb strains differentially modulate cellular susceptibility to HIV-1 infection (cis- and trans-infection), via surface receptor interaction by their cell envelope lipids. Total lipids from pathogenic (lineage 4 Mtb H37Rv, CDC1551 and lineage 2 Mtb HN878, EU127) and non-pathogenic (Mycobacterium bovis BCG and Mycobacterium smegmatis) Mycobacterium strains were integrated into liposomes mimicking the lipid distribution and antigen accessibility of the mycobacterial cell wall. The resulting liposomes were tested for modulating in vitro HIV-1 cis- and trans-infection of TZM-bl cells using single-cycle infectious virus particles. Mtb glycolipids did not affect HIV-1 direct infection however, trans-infection of both R5 and X4 tropic HIV-1 strains were impaired in the presence of glycolipids from M. bovis, Mtb H37Rv and Mtb EU127 strains when using Raji-DC-SIGN cells or immature and mature dendritic cells (DCs) to capture virus. SL1, PDIM and TDM lipids were identified to be involved in DC-SIGN recognition and impairment of HIV-1 trans-infection. These findings indicate that variant strains of Mtb have differential effect on HIV-1 trans-infection with the potential to influence HIV-1 disease course in co-infected individuals.